Visualization of Multivariate Time-Series Characteristics of Ground Loss Caused by Shield Tunneling - Zhu Wen; Xiaoli Rong; Fei Gao; Zhen Wang; Dong An (Shock and Vibration)
Ground loss due to earth pressure balance shield tunneling eventually leads to a surface settlement which can be an issue of great concern. However, the existing machine learning methods ignore the continuous and dynamic nature of EPB shield tunneling. In this work, a multivariate time-series (MTS) model for ground loss is proposed based on an analysis of factors and processes related to ground loss combined with the characteristics of original time-series data involving multiple parameters recorded by EPB shield machines in real time. A method of visualizing MTS features based on a residual network and multichannel fully convolutional neural network is also presented. The validity of the proposed ground-loss model is verified via calculation and comparison with 13 EPB shield construction projects carried out in typical urban areas featuring soft soil. Thermal maps are thus obtained to visualize the classification contributions, which provide a visual basis for feature analysis.